Heavy metal leaching behaviour and long-term environmental risk assessment of cement-solidified municipal solid waste incineration fly ash in sanitary landfill. (August 2022) - Liu, Qin; Wang, Xiaona; Gao, Ming; Guan, Yanyan; Wu, Chuanfu; Wang, Qunhui; Rao, Yi; Liu, Shu
Abstract: Cement solidification is a commonly used pre-treatment method for municipal solid waste incineration fly ash (MSWIFA) prior to sanitary landfill. However, the long-term environmental risk of cement-solidified MSWIFA blocks in the exposed scenario of zoning sanitary landfill remains unclear. In this study, the leaching characteristics of different heavy metals in cement-solidified MSWIFA blocks under deionized water and acid rain scenarios were firstly investigated. The leaching control mechanisms of heavy metals were also explored and applied to established mechanical models for the estimation of long-term environmental risk. Results revealed that Pb leaching from cement-solidified MSWIFA blocks was controlled by diffusion; Cu, Cr and As leaching was mainly controlled by surface wash-off and diffusion; and Ni leaching was mainly controlled by diffusion and dissolution. Additionally, the established bulk diffusion, first-order reaction/diffusion and diffusion/dissolution models could accurately fit the abovementioned three types of heavy metals with different leaching control mechanisms (R 2 > 0.95). Under acid rain scenarios， according to the prediction results of the calibrated models, the cumulative leaching amount of Pb in 718 d was higher than the limit in GB16889-2008, the cumulative leaching amount of Cu, Cr, As and Ni did not exceed the limit in GB 16889-2008 even in 50 years. Therefore, the long-term environmental risk was relatively high for Pb but was low for Cu, Cr, As and Ni in cement-solidified MSWIFA blocks. This finding could be attributed to the strong alkali environment of cement-solidified MSWIFA blocks (pH > 12) that induced Pb salts (e.g. Pb(OH)2 and PbSO4 ) dissolution. Therefore, the removal of partially soluble Pb salts from freshly made cement-solidified MSWIFA blocks by water or natural rainwater (e.g. without final cover system) washing in the initial landfilling stage (e.g. the leachate drainage system remains functional) is an effective countermeasure to reduce the environmental risks in zoning sanitary landfill. Graphical abstract: Image 1 Highlights: The leaching behaviour of heavy metal in cement-solidified MSWIFA was investigated. Pb leaching was mainly controlled by the diffusion mechanism. Long-term environmental risk was low for Cu, Cr, As and Ni, but high for Pb. The cumulative leaching amount of Pb in 718 d was higher than the limit in GB16889. Partially remove soluble Pb salts from the blocks reduce the zoned landfill risk.